2022
DOI: 10.1186/s13071-022-05472-8
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and behavioral activity of Anopheles mosquitoes on the slopes of Mount Cameroon

Abstract: Background Malaria remains endemic in Cameroon, with heterogeneous transmission related to eco-climatic variations, vector diversity and spatial distribution. The intensification of malaria prevention and control through the free distribution of insecticide-treated nets in recent years may have altered the composition, geographic distribution and natural infection rate of Anopheles species, with implications for malaria transmission dynamics. The present study seeks to assess the vectorial dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…Indeed, the work of Rahm and Vermilin [15] on the distribution of anopheline species in all Congolese territories identified 66 species of Anopheles, whereas Watsenga et al's [9] work, based on sentinel sites in the DRC, identified fewer species. Yet, there is evidence elsewhere (Cameroon) that a greater diversity of species can be identified when the choice of sentinel sites is based on ecological criteria [16].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the work of Rahm and Vermilin [15] on the distribution of anopheline species in all Congolese territories identified 66 species of Anopheles, whereas Watsenga et al's [9] work, based on sentinel sites in the DRC, identified fewer species. Yet, there is evidence elsewhere (Cameroon) that a greater diversity of species can be identified when the choice of sentinel sites is based on ecological criteria [16].…”
Section: Introductionmentioning
confidence: 99%